Tensions between Religion and Policy: Navigating the Public Sphere - Sambo, Usman (FISIP UIN Sunan Gunung Djati Bandung, 2023)
Research Problem: This abstract delves into the challenges posed by the integration of religion in state policy within multicultural societies. It highlights the tensions that arise when religious beliefs intersect with secular governance principles, and the dilemmas governments face in balancing religious freedom with the separation of religion and state. Research Purposes: The primary purpose of this abstract is to explore the complexities surrounding the incorporation of religion into state governance frameworks. It aims to shed light on the diverse approaches taken by governments to address these challenges and their implications for social cohesion, individual rights, and democratic governance. Research Methods: Methodologically, this abstract draws upon case studies from various countries to examine the integration of religion in state policy. It employs a qualitative analysis approach to delve into the tensions and dilemmas faced by governments in multicultural societies when dealing with issues related to religious freedom and secular governance. Results and Discussion: The abstract discusses the multifaceted issues surrounding the integration of religion in state policy, including the potential implications for social cohesion, individual rights, and democratic governance. It explores diverse approaches taken by governments and the role of dialogue, education, and policy-making in mitigating challenges. Research Implications and Contributions: This abstract provides a comprehensive overview of the challenges associated with integrating religion into state policy within multicultural societies. It invites further research and discussion on this critical aspect of multiculturalism, aiming to contribute to a deeper understanding of the complex relationship between religion, governance, and societal cohesion.